Graft rejection in pediatric penetrating keratoplasty: Clinical features and outcomes - Kusumesh, Rakhi (Oman J Ophthalmol, 2015)
PURPOSE: Early presentation of rejection facilitates early initiation of treatment which can favor a reversible rejection and better outcome. We analyzed the incidence, clinical features including rejection-treatment period and outcomes following graft rejection in our series of pediatric corneal graft. MATERIALS AND METHODS: Case records of pediatric penetrating keratoplasty (PK) were reviewed retrospectively, and parameters noted demographic profile, indication of surgery, surgery-rejection period, rejection-treatment interval, graft outcome, and complications. RESULTS: PK was performed in 66 eyes of 66 children <12 years, with an average follow-up of 21.12 ± 11.36 months (range 4-48 month). The median age at the time of surgery was 4.0 years (range 2 months to 12 years). Most of the children belonged to rural background. Scarring after keratitis (22, 33.4%) was the most common indication. Graft rejection occurred in eight eyes (12.12%) (acquired nontraumatic - 3, congenital hereditary endothelial dystrophy [CHED] - 2, nonCHED - 1, congenital glaucoma - 1, regraft - 1). The mean surgery-rejection period was 10.5 ± 7.3 months and mean rejection-treatment interval was 10.9 ± 7.02 days. CONCLUSION: This study showed irreversible graft rejection was the leading cause of graft failure of pediatric PK. Though, the incidence (12.1%) of graft rejection in current study was not high, but the percentage of reversal (25%) was one of the lowest in literature because of delayed presentation and longer interval between corneal graft rejection and treatment. In addition, categorization of the type of graft rejection was very difficult and cumbersome in pediatric patients.